Assessing Information Needs Regarding Metabolic Syndrome Among Gynecological Cancer Survivors: A Concurrent Mixed Method. Issue 2 (March 2019) - Jang, Insil; Kim, Ji-Su; Kim, Minhae; Lee, Eunkyung
Abstract : Background: Cancer survivors have an increased risk of non–cancer-related deaths, particularly metabolic syndrome (MetS). Objective: We aimed to assess knowledge deficits regarding metabolism-related diseases among gynecological cancer survivors and the preferred source of health information. Methods: Using a mixed methods approach, 70 participants responded to a structured modified version of the MetS questionnaire. We conducted 28 semistructured interviews of gynecological cancer survivors with MetS. Responses were independently coded by 2 researchers, including MetS knowledge, behaviors for self-management, and preferred learning methods. Results: Metabolic syndrome was diagnosed in 17% of the participants. More than 50% of the participants wanted to learn about MetS and requested a consultation with healthcare providers, 70% reported that they had heard of MetS, and 61.4% reported that they had MetS-related knowledge (correct answer rate by MetS-related component, 50%). The level of MetS-related knowledge was poor in both the quantitative and qualitative data. Most of the participants defined MetS-related self-management health behaviors as regular eating and exercise in their own words. Participants mostly wanted exercise management (29% of the participants), followed by dietary life management (27.4%), stress management (17.4%), weight management (13.7%), definition and diagnostic methods of MetS (9.1%), and smoking and drinking management (3.3%). Participants wished to use a handbook in small groups or receive counseling by healthcare providers. Conclusion: We observed poor awareness and knowledge level and the need for information regarding MetS among gynecological cancer survivors. Implications for Practice: An educational handbook or counseling could effectively improve self-management of health-related behaviors.